THE ROLE OF STORIES IN THE DEVELOPMENT OF SPEECH IN PRESCHOOL CHILDREN - Maziyayeva Mukaddasxon Esonovna (Zeta Repository, 2023)
The article discusses the influence of stories on the development of the speech of a preschool child.